Analisis Intrinsik Tiga Lagu dalam Pembelajaran Bahasa Jerman - Nursida Nursida; Syamsu Rijal; Wahyu Kurniati Asri (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. This research is qualitative descriptive research. The purpose of this study is to find out the intrinsic elements of the song, namely the theme, tone, feelings, and mandate contained in the song. The data sources in this study are primary data and secondary data. The primary data sources are three songs, namely